PERIOD1 coordinates hippocampal rhythms and memory processing with daytime. Issue 6 (4th March 2014) - Rawashdeh, Oliver; Jilg, Antje; Jedlicka, Peter; Slawska, Jolanta; Thomas, Lukas; Saade, Anastasia; Schwarzacher, Stephan W.; Stehle, Jörg H.
ABSTRACT In species ranging from flies to mammals, parameters of memory processing, like acquisition, consolidation, and retrieval are clearly molded by time of day. However, mechanisms that regulate and adapt these temporal differences are elusive, with an involvement of clock genes and their protein products suggestive. Therefore, we analyzed initially in mouse hippocampus the daytime‐dependent dynamics of parameters, known to be important for proper memory formation, like phosphorylation of the "memory molecule" cyclic adenosine monophosphate (cAMP) responsive element binding protein (CREB) and chromatin remodeling. Next, in an effort to characterize the mechanistic role of clock genes within hippocampal molecular dynamics, we compared the results obtained from wildtype (WT) ‐mice and mice deficient for the archetypical clock gene Period1 (Per1‐/‐‐mice). We detected that the circadian rhythm of CREB phosphorylation in the hippocampus of WT mice disappeared completely in mice lacking Per1. Furthermore, we found that the here for the first time described profound endogenous day/night rhythms in histone modifications in the hippocampus of WT‐mice are markedly perturbed in Per1‐/‐‐mice. Concomitantly, both, in vivo recorded LTP, a cellular correlate for long‐term memory, and hippocampal gene expression were significantly altered in the absence of Per1. Notably, these molecular perturbations in Per1‐/‐‐mice were accompanied by the loss of daytime‐dependent differences in spatial working memory performance. Our data provide a molecular blueprint for a novel role of PER1 in temporally shaping the daytime‐dependency of memory performance, likely, by gating CREB signaling, and by coupling to downstream chromatin remodeling. © 2014 Wiley Periodicals, Inc.